2019
DOI: 10.3389/fgene.2019.01273
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Automated Profiling of EpCAM Expression on Tumor-Derived Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are abundant in most biological fluids and considered promising biomarker candidates, but the development of EV biomarker assays is hindered, in part, by their requirement for prior EV purification and the lack of standardized and reproducible EV isolation methods. We now describe a far-field nanoplasmon-enhanced scattering (FF-nPES) assay for the isolation-free characterization of EVs present in small volumes of serum (< 5 µl). In this approach, EVs are captured with a cancer-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…This technique meets the rigorous demands of separating exosomes that contain specific target membrane proteins. The conclusion that capture-based techniques involving the Ep-CAM biomarker represent the best approach for separating exosomes in comparison with other methods has been widely accepted due to comprehensive analyses of the efficiency of recycling exosomes [ 47 ]. Recently, a study revealed that an approach for isolating EVs from urine using the Vn96-peptide, which specifically binds to EVs containing a heat shock protein, is much faster than traditional methods in prostate cancer, such as UC [ 48 ].…”
Section: Exosome Isolation Methodologiesmentioning
confidence: 99%
“…This technique meets the rigorous demands of separating exosomes that contain specific target membrane proteins. The conclusion that capture-based techniques involving the Ep-CAM biomarker represent the best approach for separating exosomes in comparison with other methods has been widely accepted due to comprehensive analyses of the efficiency of recycling exosomes [ 47 ]. Recently, a study revealed that an approach for isolating EVs from urine using the Vn96-peptide, which specifically binds to EVs containing a heat shock protein, is much faster than traditional methods in prostate cancer, such as UC [ 48 ].…”
Section: Exosome Isolation Methodologiesmentioning
confidence: 99%
“…Our search key identified 2224 records. Of the 18 articles eligible for qualitative synthesis 3,11,17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] , 11 were suitable for quantitative synthesis 3,11,17,18,[20][21][22][23][24][25][26] . The 904 patients included in our review comprise only nonoverlapping populations.…”
Section: Study Selectionmentioning
confidence: 99%
“…It also can be used for qualitative and quantitative determination of exosomes. Nevertheless, the storage conditions of exosomes obtained by immunoaffinity chromatography are relatively harsh and are not suitable for large-scale separation of exosomes ( Amrollahi et al, 2019 ). The method of polymer precipitation usually uses polyethylene glycol (PEG) as a medium to harvest exosomes under the centrifugation condition by reducing the solubility of the exosomes.…”
Section: Exosomes: Biogenesis Composition Function and Isolationmentioning
confidence: 99%